Respuesta :
We are asked to express r in terms of A, P, and t.
We first divide both sides of the equation by t, which gives us
[tex]\displaystyle{ \frac{A}{t}=P(1+r) [/tex],
then, dividing both sides by P, we have
[tex]\displaystyle{ \frac{A}{Pt}=1+r [/tex].
Swap the sides:
[tex]\displaystyle{ 1+r= \frac{A}{Pt}[/tex]
Finally subtracting 1 from both sides gives us
[tex]\displaystyle{ r=\frac{A}{Pt}-1[/tex].
We first divide both sides of the equation by t, which gives us
[tex]\displaystyle{ \frac{A}{t}=P(1+r) [/tex],
then, dividing both sides by P, we have
[tex]\displaystyle{ \frac{A}{Pt}=1+r [/tex].
Swap the sides:
[tex]\displaystyle{ 1+r= \frac{A}{Pt}[/tex]
Finally subtracting 1 from both sides gives us
[tex]\displaystyle{ r=\frac{A}{Pt}-1[/tex].
Answer: [tex]r=(\frac{A}{P})^{\frac{1}{t}}-1[/tex]
Step-by-step explanation
Compound interest is the addition of interest to the principal sum of a deposit or a loan.
Let P = principal amount which was taken as a loan then the accumulated amount A is given by
[tex]A=P(1+r)^t[/tex].......(1)
where, r is the rate of simple annual interest in decimal.
t is the time applied for interest.
For solving r divide both sides of equation by P in (1),we get
[tex]\frac{A}{P}=(1+r)^t\\\Rightarrow(\frac{A}{P})^{\frac{1}{t}}=1+r\\\Rightarrow\ r=(\frac{A}{P})^{\frac{1}{t}}-1[/tex].